The Effect of Abdominal Lifting Technique on Postpartum Pain at St. Carolus Summarecon Hospital - Adegi, Luthfiyah; Rukmaini; Putri Azzahroh (International Journal of Midwifery and Health Sciences, 2025)
Background: Labor pain is a subjective experience of the patient caused by uterine muscle ischemia, pulling and traction of the uterine ligaments, ovarian traction, fallopian tubes and distension of the lower part of the uterus, pelvic floor muscles and perineum. Abdominal Lifting is a stroke that is done in the opposite direction to the top of the abdomen without any pressure to the inside and is done repeatedly, with the supine position and the head slightly elevated. Objective: To determine the average value of postpartum pain in postpartum mothers before and after being given abdominal lifting technique intervention at Sint Carolus Hospital Summarecon Serpong. Methodology: Quasi-experimental research design with pretest posttest with one control group design. The sample consisted of 15 postpartum mothers, selected using purposive sampling technique. The instrument used was the Numeric Rating Scale (NRS). Data were analyzed using the Paired Sample T-Test. Results: There is a difference in the average postpartum pain scale of postpartum mothers before and after the intervention in one group with a p-value of 0.024 <0.05. There is a difference in the scale of postpartum pain in the group before the abdominal lifting technique intervention, which is 7,20 and the group after the intervention, which is 2,67 after being carried out for 7 days. Conclusion: Providing abdominal lifting technique intervention is effective in reducing postpartum pain in postpartum mothers. Suggestion: Midwives can provide complementary care for postpartum mothers with postpartum pain in the form of abdominal lifting techniques carried out for 7 days. Keywords: Postpartum Pain, Abdominal Lifting, Postpartum Mothers References: 44 (2019-2024)